2015
DOI: 10.1007/s10006-015-0499-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced somatosensory impairment by piezosurgery during orthognathic surgery of the mandible

Abstract: Piezosurgery caused reduced somatosensory impairment and a faster recovery of somatosensory functions in the present investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
11
2
4
Order By: Relevance
“… 74 There are many other indications for the use of the piezoelectric device in maxillofacial surgery. 75 An increasing number of studies show the use of the piezoelectric device in orthognathic surgery, 76 80 and even research on the use of computer-assisted piezoelectric surgery for osteotomies has been published. 81 The advantage of high-precision cutting and reduced risk of nerve damage are very convincing arguments to use the piezoelectric device.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“… 74 There are many other indications for the use of the piezoelectric device in maxillofacial surgery. 75 An increasing number of studies show the use of the piezoelectric device in orthognathic surgery, 76 80 and even research on the use of computer-assisted piezoelectric surgery for osteotomies has been published. 81 The advantage of high-precision cutting and reduced risk of nerve damage are very convincing arguments to use the piezoelectric device.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Geha et al reported an 80% complete neurosensory recuperation 2 months after BSSRO [17]. Brockmeyer et al also showed less somatosensory impairment and faster recovery of somatosensory function using piezosurgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies presented a methodological quality and risk analysis that was considered good; these two studies had a score of 5 36,37 . Of the 12 selected articles, two reported retrospective studies 38,39 , which impairs randomization and blinding.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies in which the two types of surgical instruments were compared, the results obtained were compared between different patients 10,12 , or the comparison was made in the same patient where one side of the SSO had been performed with a saw and the contralateral side with a piezoelectric device 9,36,37 . Two articles reported 34 cases of rotation of the occlusal plane (Table 2) 10,39 .…”
Section: Type Of Movement and Manufacturers Of The Instruments Usedmentioning
confidence: 99%